1987
DOI: 10.1007/bf00160684
|View full text |Cite
|
Sign up to set email alerts
|

Growing old and lonely in different societies: Toward a comparative perspective

Abstract: The main argument of this paper is that the subjective experience of loneliness among older people must be analyzed in relation to the overall value system of society or the subcultural values of particular segments of society. Cultural or subcultural value systems are contrasted in terms of whether they give priority to individualistic values or to collective values such as family or community bonds. These differences in value systems result in important differences in people's social contacts and socioemotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 17 publications
(15 reference statements)
4
69
0
1
Order By: Relevance
“…Several authors point to the importance of considering people's frames of reference and normative orientations in the cultural context of countries under investigation (Jylha and Jokela 1990;Johnson and Mullins 1987). Loneliness occurs when the quality of one's social relationships falls short of the expected or desired quality of social relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors point to the importance of considering people's frames of reference and normative orientations in the cultural context of countries under investigation (Jylha and Jokela 1990;Johnson and Mullins 1987). Loneliness occurs when the quality of one's social relationships falls short of the expected or desired quality of social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Such cultures may prevent loneliness by promoting social integration. However, as others have noted (Johnson and Mullins 1987;Jylha and Jokela 1990), the high expectations of strong ties may increase feelings of loneliness if these expectations are not met. Placing a T. Hansen, B high value on close family ties may thus make matters worse for seniors in countries with high rates of widowhood, decreasing fertility rates, and increasing out-migration (see ''Appendix'').…”
Section: Introductionmentioning
confidence: 89%
“…The relationship between childlessness and psychological well-being and life satisfaction may differ in contexts with a variety of cultural value orientations (Cheung and Leung 2004;Ji et al 2002;Johnson and Mullins 1987). For example, dominated by the pronatalist Confucian culture, Chinese society stresses the value of children in the lives of their elderly parents in terms of filial piety (Ikels 2004;Sung 1998).…”
Section: Previous Studies and Present Research Questionmentioning
confidence: 97%
“…Research has shown that the prevalence of loneliness varies between cultural groups (Johnson and Mullins 1987). Within Europe, reported levels of loneliness are highest in the countries of the former Soviet Union at around 25-30% and lowest in the countries of Northern Europe, rates of about 10% with the southern European countries occupying an intermediate position reporting rates of 15-20% (Yang and Victor 2011;Sundström et al 2009).…”
Section: Introductionmentioning
confidence: 96%